Pendekatan Metode AHP untuk Pemilihan Vendor Transportasi di CV. MJ - Muhammad Hafidz Yusuf; Moh. Ririn Rosyidi; M. Ajir Muzakki (Jurnal Optimalisasi, 2026)
CV. MJ is a company engaged in the processing of one of the materials used as a mixture for fertilizer factories, namely minerals in the form of clay. Researcher observations conducted at CV.MJ found problems related to vendor partners, namely: late delivery from the time agreed by both parties, price discounts imposed by vendor partners, the quality of the transportation fleet from vendor partners, and services provided by vendor partners that are not optimal. Based on these problems, this study aims to select a transportation vendor using the AHP method. The decision-making method with AHP is basically this technique breaks down complex problems into a hierarchy, then gives priority to various options and criteria and determines the decision choice based on the highest weight. In this study, several criteria were used, namely cost, timeliness, guarantee of security of goods, and infrastructure of the transportation fleet. The results of this study show each weight on these criteria, namely cost of 0.26, timeliness of 0.14, guarantee of security of goods of 0.53, and infrastructure of the transportation fleet of 0.06. Of these criteria, the one with the highest weight is the guarantee of security of goods of 0.53. The assessment results show that transportation vendor partners at CV.MJ have a higher weight. MJ has SD Trans with a weight of 0.42, Piter Logistic with a weight of 0.14, Aris Trans with a weight of 0.19, and Geci Express with a weight of 0.26. Based on the weight assessment, SD Trans has the highest weight, with a score of 0.42. The researcher's recommendation for CV.MJ is to choose SD Trans as a priority vendor partner because it has the highest weight among CV.MJ's transportation vendor partners.